No QTc Prolongation With Zanubrutinib: Results of Concentration‐QTc Analysis From a Thorough QT Study in Healthy Subjects. Issue 5 (8th April 2020) - Mu, Song; Darpo, Borje; Tang, Zhiyu; Novotny, William; Tawashi, Manal; Xue, Hongqi; Willett, Michael; Lin, Leo; Sahasranaman, Sri; Ou, Ying C.
Abstract : This thorough QT (TQT) study evaluated the effect of zanubrutinib on electrocardiogram (ECG) parameters by using concentration‐QTc (C‐QTc) analysis as the primary analysis for this study. Part A of the study determined the safety and tolerability of a single supratherapeutic dose of zanubrutinib (480 mg) in healthy volunteers. Part B was a randomized, blinded, placebo‐controlled and positive‐controlled, four‐way crossover, TQT study of single therapeutic (160 mg) and supratherapeutic (480 mg) doses of zanubrutinib, placebo, and open‐label moxifloxacin 400 mg. Thirty‐two participants received at least 1 dose of zanubrutinib, and 26 participants completed all 4 periods. Zanubrutinib did not have any effect on heart rate or cardiac conduction (pulse rate, QRS interval, or T‐wave morphology) and was generally well‐tolerated. Using C‐QTc analysis, the predicted placebo‐corrected change‐from‐baseline QT interval using Fridericia's formula (ΔΔQTcF) was −3.4 msec (90% confidence interval: −4.9 to −1.9 msec) at peak concentrations of the 480 mg dose. A QT effect (ΔΔQTcF) exceeding 10 msec could be excluded within the observed concentration range at 160 and 480 mg doses. Assay sensitivity was established by moxifloxacin with 90% lower bound exceeding 5 msec. Implementing a C‐QTc analysis prospectively in this TQT study resulted in a substantially smaller sample size to maintain a similar study power as shown in the traditional time‐point analysis. A single 160‐mg or 480‐mg zanubrutinib dose did not prolong the QTc interval or have any other clinically relevant effects on ECG parameters.